Fear avoidance beliefs, anxiety, and depression in healthy individuals and persons with vestibular disorders across cultures - Van Laer, Lien; Dunlap, Pamela M.; Vereeck, Luc; Hendriks, Erwin; Sluydts, Morgana; Whitney, Susan L. (Frontiers in Neurology, 2023)
Background/introduction In persons with vestibular disorders, disturbed vestibular input and accompanying dizziness can be associated with anxiety or depression. To avoid dizziness, persons with vestibular disorders can develop mal-adaptive fear avoidance behaviors which can negatively influence daily life functioning. The aims of this study were to (1) document different psychological factors in patients with vestibular disorders and healthy adults across cultures and (2) to assess the convergent validity of the 9-item Vestibular Activities Avoidance Instrument (VAAI), which quantifies fear avoidance beliefs. Methods Psychological factors and disability were measured in Dutch-speaking healthy adults and English- and Dutch-speaking persons with vestibular disorders using the VAAI, the Dizziness Handicap Inventory (DHI), the Hospital Anxiety and Depression Scale (HADS) and the Activities-Specific Balance Confidence Scale (ABC). The convergent validity of the VAAI was investigated by performing correlation analyses between the VAAI, the DHI, the HADS, and the ABC. Results A total of 151 Dutch-speaking healthy adults, 404 English-speaking participants with vestibular disorders, and 126 Dutch-speaking participants with vestibular disorders were included. Participants with vestibular disorders presented with higher levels of fear avoidance beliefs (VAAI), perceived disability (DHI), anxiety and depression (HADS), and lower confidence during balance activities (ABC) compared to healthy adults. Regarding the convergent validity of the VAAI, there were moderate to strong correlation coefficients (r = 0.39–0.74) between fear avoidance and the DHI, HADS, and ABC in participants with vestibular disorders. Conclusions Participants with vestibular disorders report a higher psychological burden compared to healthy adults. These results emphasize the importance of assessing psychological factors in persons with vestibular disorders. In addition, evidence was provided for convergent validity, supporting the VAAI as a valid outcome measure across cultures.